Specification of a new de‐stoner machine: evaluation of machining effects on olive paste's rheology and olive oil yield and quality. (1st April 2016) - Romaniello, Roberto; Leone, Alessandro; Tamborrino, Antonia
Abstract: BACKGROUND: An industrial prototype of a partial de‐stoner machine was specified, built and implemented in an industrial olive oil extraction plant. The partial de‐stoner machine was compared to the traditional mechanical crusher to assess its quantitative and qualitative performance. The extraction efficiency of the olive oil extraction plant, olive oil quality, sensory evaluation and rheological aspects were investigated. RESULTS: The results indicate that by using the partial de‐stoner machine the extraction plant did not show statistical differences with respect to the traditional mechanical crushing. Moreover, the partial de‐stoner machine allowed recovery of 60% of olive pits and the oils obtained were characterised by more marked green fruitiness, flavour and aroma than the oils produced using the traditional processing systems. CONCLUSION: The partial de‐stoner machine removes the limitations of the traditional total de‐stoner machine, opening new frontiers for the recovery of pits to be used as biomass. Moreover, the partial de‐stoner machine permitted a significant reduction in the viscosity of the olive paste. © 2016 Society of Chemical Industry